Uporaba pravil FIDIC pri oddaji javnih naročil - Kranjc, Vesna (Pravni letopis, 2020)
The article introduces the role of FIDIC Conditions and business relationships which could be subordinated to the FIDIC Red, Yellow and Silver Book. Under Red Book the contractor constructs the work in accordance with a design provided by the employer. Under Yellow and Silver Book contractor has the responsibility for design and work performance, but plan and work performance should be alligned with employer`s requirements. The use of FIDIC acts also faciliates the award of public procurement contracts. However, the regulation of individual issues according to the FIDIC rules requires special attention and a different regulation in public procurement contracts. The position of nominated subcontractors, the reference condition on the performance of previous works according to FIDIC acts and the limited possibilities for concluding a settlement in public procurement are discussed.
Keywords: gradbeništvo; javna naročila; javni sektor